Adjusting to Global Economic Change The Dangerous Road Ahead - Levine, Robert A. (RAND Corporation, 2009)
The author combines macroeconomic history since the Great Depression with a brief exposition of economic theory that stems from and explains that history, and explores how that experience may apply to the present economic crisis. He warns that we may again be headed for stagflation and makes suggestions for escaping the worst effects of the crisis.